Controlling An-Inverted Pendulum System Using A Microcontroller - Mohamad Zahari, Ahmad Amirul (Universiti Sains Malaysia, 2022)
A self-balancing robot is basically an inverted pendulum. It can balance better if the centre of mass is higher than the wheel axels. A greater centre of mass equals a higher moment of inertia, which equals a lower angular acceleration. Particularly during movement, a well-implemented TWSB robot is able to maintain an upright stance. The majority of papers focus on either creating controllers through the implementation of low-level microcontroller units, such as Arduino Uno, or on dynamic modelling features in which simulation findings are used to decide results rather than real-world applications. This study will concentrate on comparing simulation results to the actual installation of a TWSB robot since fewer researchers have done so. This project intends to study the performance of the produced TWSB robot, examine the applicability of MATLAB to the programming of the TWSB robot, and compare the performance of the TWSB robot to the simulation results from MATLAB. Concurrently, a comparison is made between the present project and earlier work to assess the advantages and disadvantages of each. In this instance, a TWSB robot is constructed utilising an Arduino UNO microcontroller and a PID algorithm controller. The MPU 6050 gyroscope is calibrated before being mounted to the robot in order to maximise the accuracy of the acquired results by determining offset values. MATLAB is used to establish the appropriate control term values for the PID controller in order to replace the human tuning procedure and facilitate the stabilisation of the TWSB robot. According to the results, control term values of Kp = 64, Ki = 45, and Kd = 1.3 are adequate to maintain the posture of the TWSB robot, enabling it to maintain stability on a variety of surfaces, including flat and uneven surfaces, with or without the application of forces and obstructions.